PENGARUH PENGAWASAN, KOMUNIKASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI SUB BIDANG PENGAWASAN BARANG DI DISPERINDAG PROVINSI RIAU - aznuriyandi aznuriyandi (Universitas Lancang Kuning, 2021)
This research was conducted at the Division of Goods Department of Industry and Trade of the Province of Riau, Lancang Kuning Tower Building, 5th Floor, Jalan Sudirman No. 460, Pekanbaru, Riau Province. Purpose and benefits of this research is Knowing Effect Control, Communications and Performance Against Employee Competency sub field supervision Disperindag goods in Riau province in the future. Data collection techniques used in this research is to use the data collection tool in the form of questionnaires and interviews, and the sampling method used by the census techniques / saturation sampling that samples drawn based on population as a whole. So the sample in this study were as many as 85 employees. The data analysis used is multiple linear regression analysis with the help of SPSS software vers. 17. Besides, do also partial test (t test). From the results of research on the influence of Control, Communication and Competence can improve the performance of Goods Sub-Sector Employees In Riau Province Disperindag Variable Control (X1) obtained t amounted to 11 508 greater than ttable is 1.662. This means that the independent variable (Supervision) can explain the dependent variable (performance) and there is significant independent variable on the dependent variable being tested at 61.6%. Communication variables (X2) obtained t amounted to 4,790 bigger than t table is 1.662. This means that the independent variable (Communications) can explain the dependent variable (performance) and there is significant independent variable on the dependent variable being tested at 25.3%. Variable Competence (X3) obtained t for 4390 is greater than ttable is 1.662. This means that the independent variable (Competence) can explain the dependent variable (performance) and there is significant independent variable on the dependent variable being tested at 22.2%. hypothesis test result shows that the Fhitung greater than Ftable is 370 632> 2.72, meaning that proved the regression model used successfully explain the influence of independent variables (X1, X2 and X3) together significantly on the dependent variable (Y). The influence of the dependent variable can be seen from the coefficient of determination (R square), the amount is 0932 That is 93.2% while the remaining 6.8% is influenced by other variables not examined in this study. Keywords: Control, Communication, Competence, Performance.